Auditory-visual temporal integration as a function of distance: no compensation for sound-transmission time in human perception - Lewald, Jörg; Guski, Rainer (Neuroscience letters, 2004)
In a psychophysical outdoor experiment with human subjects, the point of subjective simultaneity (PSS) of auditory and visual stimuli was measured for distances from 1 to 50 m. Repetitive sound and light pulses were presented with various stimulus-onset asynchronies, and subjects judged which modality came first. With increasing distance of the stimuli the PSS shifted in a linear relation toward delays of the light behind the sound. The slope of the regression line (3 ms/m) almost exactly corresponded to that of the temporal disparities resulting from the lower velocity of sound compared to light. These data refute the hypothesis proposed recently that there could be an ‘implicit estimation’ of sound-arrival time. The brain seems to eliminate such crossmodal temporal disparities by the integration of auditory and visual stimuli that fall into a time window, but not by specific compensatory processes that use an estimate of the sound delay.